Young Adults’ Knowledge and Attitudes Regarding “Music” and “Loud Music” Across Countries: Applications of Social Representations Theory - Manchaiah, Vinaya; Zhao, Fei; Ratinaud, Pierre (Frontiers in Psychology, 2019)
Exposure to loud music, especially by young people, has significantly increased in recent years as a result of (a) advancements in technology in terms of personal music players and smart mobile phones, and (b) streaming of music through these devices. The World Health Organization (WHO) estimates that some 1.1 billion teenagers and young adults are at risk of developing hearing loss due to exposure to recreational noise such as music. It is suggested that knowledge and attitude of young adults towards music has bearing upon their music listening habits and thereby influences who is at risk of developing music induced hearing loss. Hence, researchers from various fields have tried to understand the knowledge and attitude of young adults regarding loud music. However, there is some criticism of attitude studies as there is little relation between expressed attitude and behavior. Some recent studies have explored the social representations of music and loud music using the Social Representations Theory (SRT). It has been suggested that social representation is more fundamental than attitude (or in other words social representation informs attitude), hence, it has a better relation to behavior. The current paper: (1) provides an overview of studies on knowledge and attitude of young adults towards loud music, (2) discusses the limitations of attitude theories and introduces SRT, and (3) provides a summary of social representation studies on ‘music’ and ‘loud music’ in young adults from different countries.